2011
DOI: 10.3201/eid1704.101353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Hygiene Campaigns on Incidence of Laboratory-confirmed Influenza and Absenteeism in Schoolchildren, Cairo, Egypt

Abstract: To evaluate the effectiveness of an intensive hand hygiene campaign on reducing absenteeism caused by influenza-like illness (ILI), diarrhea, conjunctivitis, and laboratory-confirmed influenza, we conducted a randomized control trial in 60 elementary schools in Cairo, Egypt. Children in the intervention schools were required to wash hands twice each day, and health messages were provided through entertainment activities. Data were collected on student absenteeism and reasons for illness. School nurses collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
243
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(255 citation statements)
references
References 65 publications
3
243
2
7
Order By: Relevance
“…13 School-based randomized trials in China and Egypt found lower rates of both absenteeism and absenteeism related to certain illnesses among pupils that participated in handwashing interventions. 10,12 A handwashing trial among preschool children in Israel found no effect on overall absenteeism or absenteeism due to illness. 14 In Kenya, no overall effect of a comprehensive WASH intervention was found, although a reduction in absence was found among girls.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…13 School-based randomized trials in China and Egypt found lower rates of both absenteeism and absenteeism related to certain illnesses among pupils that participated in handwashing interventions. 10,12 A handwashing trial among preschool children in Israel found no effect on overall absenteeism or absenteeism due to illness. 14 In Kenya, no overall effect of a comprehensive WASH intervention was found, although a reduction in absence was found among girls.…”
Section: Introductionmentioning
confidence: 77%
“…Our findings are comparable with research showing that school WASH interventions are associated with lower rates of self-reported diarrhea and influenza. 9,12 In addition, we found that among pupils who had been absent in the last week, the odds of reporting absence due to diarrhea was 27% lower in beneficiary schools than in comparison schools. These data are comparable with findings of reduced absence due to diarrhea and other illness after school WASH interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…School children are important agents in spreading the disease either among themselves or to the members of the family and the community. Hence, the emphasis of hand washing is very important (Talaat et al, 2011). Majority (77.4%) subjects admitted their parents did not practice the 7 steps of hand washing at home.…”
Section: Discussionmentioning
confidence: 99%